Analysis of Financial Statements in Measuring Financial Performance at PT. ACE Hardware Indonesia Tbk. - Moh. Djufri Dapi, SE, M.Si, Ak, Ca (Cita konsultindo, 2022)
Financial Report Is an accounting final process that plays an important role in measuring and assessing the work in every company, financial report analysis is a form used in assessing company performance whether a company is in a good or bad position. This study aims to determine the financial performance of the company, namely PT ACE Hardware Indonesia by using financial ratio analysis at PT ACE Hardware Indonesia from 2018-2021. The data analysis technique used is a quantitative descriptive method using measurements of the ratio of liquidity, solvency and profitability. Based on research results, the liquidity ratio in 2018-2021 is said to be unstable because there are ups and downs every year. The results of the solvency ratio are also said to be the same as the previous results where these results are said to be fluctuations or conditions that occur every year. and the profitability results are said to be not good because every year it has decreased.